SEARCHING FOR PERIODIC AND QUASI-PERIODIC ORBITS OF SPACECRAFTS ON THE HAUMEA SYSTEM - Sanchez, Diogo M.; Prado, Antonio F. B. A.; Yokoyama, Tadashi [UNESP]; Majji, M.; Turner, J. D.; Wawrzyniak, G. G.; Cerven, W. T. (Univelt Inc, 2016)
In this work, we explore regions around the two moons of the dwarf planet Haumea, Namaka and Hi'iaka, in order to provide options for a mission to this system. Using a model with the perturbation of the Sun, Namaka and Hi'iaka, and the gravitational potential of Haumea up to degree and order four, we map the survival time of a spacecraft in a wide range of initials semi-major axis and inclination. Then, we found apparently stable orbits in the vicinity of Namaka and Hi'iaka. Finally, using the restricted three body problem, Poincare sections were made in order to find periodic and quasi-periodic orbits around these two moons.